Kinerja Kepala Desa dalam Pembangunan Infrastruktur Desa Sidorukun Kecamatan Randangan Kabupaten Pohuwato - Umar Sune (Universitas Islam Darul Ulum Lamongan, 2019)
The problem in this study is the Performance of the Village Head in Infrastructure Development in Sidorukun Village, Randangan District, Pohuwato Regency and What are the inhibiting factors. As for the purpose of this study is to determine the Performance of the Village Head in Sidorukun Village Infrastructure Development, Randangan Subdistrict, Pohuwato Regency and its inhibiting factors. The design of this study the authors chose the type of descriptive qualitative research, using descriptive qualitative study methods that describe methods that are directed to solve problems by describing or describing what the results of the study are. Data collection techniques in this study use several ways, among others, observation, namely, to look directly at and find information that is related to research, interviews, that is, to obtain information directly from respondents through a two-way communication process, namely questionnaire, list of questions from researchers to respondents either directly or indirectly. Analysis of the data where the data obtained in the field will be analyzed qualitatively. Qualitative analysis is used to describe the efforts made in the form of the performance of the village head in infrastructure development in Sidorukun Village, Randangan sub-district, Pohuwato Regency. The results obtained show that the Performance of the Village Head in Infrastructure Development in Sidorukun Village, Randangan District, Pohuwato Regency. Seen in Coordinating community empowerment activities, Coordinating efforts to implement peace and public order and Coordinating the application and enforcement of laws and regulations is still lacking or not working as well as in village infrastructure development there is active participation of the community in development, the existence of a sense of community responsibility for development and community capacity villages to develop can be improved, this does not work and the inhibiting factors where the Internal Factors are Awareness or Willingness Factors and External Factors namely Government Leadership.